The Teaching and Methodical Support of Management of Training Process of Legal Profile Students - Magomedov, Guseyn B.; Dzhamalova, Bika B.; Alieva, Patimat Sh.; Mishchenko, Elena V.; Belonovskaya, Izabella D. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the new requirements for the training of lawyers who solve professional tasks and promote a legal culture. The purpose of the article is to develop a mechanism to assess the quality of teaching and methodical support to control the process of legal profile students training. The survey methods, expert assessment are used in the study. The study involved 450 teachers, 402 students, 448 experts. The main results of the study are to identify the functions, stages, criteria, tools, pedagogical conditions (creation of intra-university quality management system of the training; the willingness of teachers to evaluate the quality of teaching and methodical support, monitoring of the quality of teaching and methodical support) to assess the quality of training and methodological support. This study provides important lessons. First, pedagogical assessment of the quality of teaching and methodical support to manage the process of law profile students' training is conditioned by the need to form the ability to analyze the situation and give it legal qualifications; construct an algorithm of actions based on the rule of law; offer solutions' variants to the problem through legal mechanisms. Second, the mechanism to assess the quality of training and methodological support includes a base for carrying out, the definition of the functions and criteria of educational evaluation. Keywords: Knowledge Society, Teaching and Methodical Support, Training of Lawyers. JEL Classifications: I21, I25, I28